FRI0138 A Psychometric Analysis of Outcome Measures in Trials of Peripheral Spondyloarthritis. (10th June 2014) - Ramiro, S.; Turina, M.; Baeten, D.L.; Mease, P.; Paramarta, J.E.; Song, I.-H.; Pangan, A.L.; Landewe, R.
Abstract : Background: In peripheral spondyloarthritis (pSpA), no specific efficacy endpoint has been developed representing improvement in arthritis, enthesitis, and/or dactylitis. Objectives: To assess the discriminatory aspects of disease activity measures and response criteria between adalimumab (ADA) and placebo (PBO) in 2 studies of patients (pts) with pSpA. Methods: ABILITY-2 is an ongoing randomized controlled trial of ADA in pts with pSpA fulfilling ASAS peripheral SpA criteria. Primary endpoint was PSpARC40 at wk 12, defined as ≥40% improvement from baseline (BL) (≥20 mm absolute improvement on a visual analog scale) in Patient Global Assessments of Disease Activity (PGA) and Pain (PGA-pain) and ≥40% improvement in ≥1 of the following: swollen joint (SJC) and tender joint counts (TJC); enthesitis count; or dactylitis count. In an investigator-initiated study (AMC) in the Netherlands, pts fulfilling ESSG and/or AMOR criteria for SpA for ≥3 months but not criteria for ankylosing spondylitis or psoriatic arthritis were randomized to ADA or PBO. Primary endpoint was change in PGA at wk 12. Analyses to determine the discriminatory capacity of disease activity measures between ADA and PBO groups included standardized mean difference (SMD) of the mean change from BL and Guyatt's effect size (ES); for categorical response criteria Pearson's χ 2 between treatments were calculated. The higher the SMD/ES and χ 2, the higher the discriminatory capacity. Variables evaluated included PGA, PGA-pain, Physician's Global Assessment of Disease Activity (PhGA), CRP, TJC, SJC, BASDAI, SF-36, HAQ-S, ASDAS, PSpARC40/50/70, ASDAS major improvement/inactive disease, and BASDAI50. Results: ABILITY-2 randomized 165 pts (ADA 84, PBO 81); AMC enrolled 40 pts (ADA 20, PBO 20). Among the continuous variables, ASDAS discriminates better than BASDAI or individual measures such as PGA, or CRP (Table). For clinical response criteria, PSpARC40, PSpARC50, ASDAS inactive disease and BASDAI50 performed well in differentiating between ADA vs. PBO treatment. Conclusions: The PSpARC response criteria developed specifically for pSpA, as well as outcome measures developed for axial SpA, such as ASDAS and to some extent BASDAI, have good discriminatory ability in patients with pSpA. The performance of the PhGA in both trials suggests that inclusion of the physician's perspective is also important in pSpA. Acknowledgements: AbbVie funded the ABILITY-2 study (NCT01064856 ), contributed to its design and was involved in the collection, analysis, and interpretation of the data, and in the writing, review, and approval of the publication. AbbVie provided adalimumab and matching placebo for the AMC study. Medical writing support was provided by Kathleen V. Kastenholz, PharmD, MS, of AbbVie. Disclosure of Interest: S. Ramiro: None declared, M. Turina: None declared, D. Baeten Grant/research support: AbbVie, BMS, Boehringer Ingelheim, Centocor, Janssen, MSD, Novartis, Pfizer, and UCB, Consultant for: AbbVie, BMS, Boehringer Ingelheim, Centocor, Janssen, MSD, Novartis, Pfizer, and UCB, Speakers bureau: AbbVie, BMS, Boehringer Ingelheim, Centocor, Janssen, MSD, Novartis, Pfizer, and UCB, P. Mease Grant/research support: AbbVie, Amgen, Biogen Idec, Bristol Myers, Celgene, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, and Vertex, Consultant for: AbbVie, Amgen, Biogen Idec, Bristol Myers, Celgene, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, and Vertex, Speakers bureau: AbbVie, Amgen, Biogen Idec, Bristol Myers, Celgene, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, and Vertex, J. Paramarta: None declared, I.-H. Song Shareholder of: AbbVie, Employee of: AbbVie, A. Pangan Shareholder of: AbbVie, Employee of: AbbVie, R. Landewe Consultant for: AbbVie, Amgen, BMS, Centocor, GSK, Merck, Novartis, Pfizer, Roche, Schering-Plough, UCB, and Wyeth, Employee of: owner of Rheumatology Consultancy bv DOI: 10.1136/annrheumdis-2014-eular.1384